2021
DOI: 10.1002/cjp2.198
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐type granulosa cell tumor of the ovary: a FOXL2‐centric disease

Abstract: Adult-type granulosa cell tumors (aGCTs) account for 90% of malignant ovarian sex cord-stromal tumors and 2-5% of all ovarian cancers. These tumors are usually diagnosed at an early stage and are treated with surgery. However, one-third of patients relapse between 4 and 8 years after initial diagnosis, and there are currently no effective treatments other than surgery for these relapsed patients. As the majority of aGCTs (>95%) harbor a somatic mutation in FOXL2 (c.C402G; p.C134W), the aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
1
34
0
6
Order By: Relevance
“…These findings suggest that tumors harboring TP53 mutations may be a high-grade subgroup of aGCT. It is noteworthy however, that other studies have not observed mutations in TP53 at similar frequencies [2,88].…”
Section: The Genomic Landscape Of Gctmentioning
confidence: 62%
See 3 more Smart Citations
“…These findings suggest that tumors harboring TP53 mutations may be a high-grade subgroup of aGCT. It is noteworthy however, that other studies have not observed mutations in TP53 at similar frequencies [2,88].…”
Section: The Genomic Landscape Of Gctmentioning
confidence: 62%
“…In a recent study by Pilsworth et al, the authors used a combination of whole genome sequencing and targeted sequencing [88], and reported a similar frequency of KMT2D inactivating mutations as that of the Hillman et al study [86] (10.8% compared to 13.9%). The difference between the two studies however was that in this study, there was no association of the KMT2D mutation with recurrence [88]. This is consistent with another published study [89] which also showed no association of this gene mutation with recurrent disease.…”
Section: The Genomic Landscape Of Gctmentioning
confidence: 89%
See 2 more Smart Citations
“…The mice developed a highly penetrant phenotype of [6,23] AGCTs have a low mutation burden. If FOXL2 were a TSG, a higher mutational load would be expected [24] FOXL2 localisation and transactivation are not affected by C134W mutation in AGCTs [25] No FOXL2 cytoplasmic mislocalisation and protein aggregation [25] AGCT, adult-type granulosa cell tumour; BPES, blepharophimosis, ptosis, and epicanthus inversus syndrome; JGCT, juvenile granulosa cell tumour; OG, oncogene; TSG, tumour suppressor gene.…”
Section: Resultsmentioning
confidence: 99%